Response of river water quality to landscape features in a subtropical hilly region - Biao Li; Xiaolei Huang; Qiang Zhong; Xiuxiu Wu (Scientific Reports)
Abstract Landscape features have a profound impact on river water quality. However, its impact in subtropical hilly region is unclear. Here, water quality data from 15 catchments were obtained based on a typical subtropical hilly area, the upper Ganjiang River basin. The landscape features in the catchment and buffer zone were calculated, and its effects on river water quality were investigated using redundancy analysis (RDA) and multiple linear regression (MLR) model. Catchment landscape features were found to better explain overall water quality changes compared to buffer zone, and landscape features were found to explain water quality changes more in winter than in summer. Moreover, within the buffer zone, the percentage of grassland had the greatest impact on winter water quality (72.8%), while at the catchment scale, the aggregation index (AI) of grassland contributed the most to changes in winter water quality (31.6%). Nonparametric change-point analysis (nCPA) was used to identify thresholds of landscape features that lead to abrupt changes in water quality. It was found that river water quality can be improved when the percentage of grassland > 0.193%, the largest patch index (LPI) of forest > 7.48% at the buffer zone or the percentage of impervious surfaces < 2.92%, the AI of forest > 98.6% at the catchment scale. This study demonstrated the pivotal role in enhancing river water quality by implementing informed and effective landscape planning for conservation implementation.